Me and My VE, Part 4. (September 2016) - Strater, Laura; Frederick, Christina M; Vaughn-Cooke, Monifa; Bliss, Jim; Shah, Smruti
Virtual environments, augmented reality, serious games, simulations, and other digitally mediated experiences are revolutionizing the way that we work, learn, and interact with people and systems. The employment of these technologies is driving innovation in research, training, education, evaluation, and various business endeavors. This session will provide a brief overview of some of the diverse uses of virtual environments (VEs) in an alternate demonstration format that leaves just over half of the session time for hands on, interactive demonstrations. Unlike most demonstration sessions, where possible, we encourage session attendees to personally interact with the demonstrations. The session will begin with demonstrators providing a brief description of their VE and how they've used it to address a unique need. At the conclusion of the description portion of the session, each VE will be set up at a demonstration station in the room, and session attendees are encouraged to engage with both the demonstrations for a hands on interaction with the VE and with the demonstrators to get more information about the development and use of the VE, and stimulate discussion on how the concepts, methods, and tools can be used to solve additional problems or business needs.